Exploring Innovation Activities in Hospitality Industry in Northern Cyprus - Namjooyan, Shabnam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
The aim of this study is to find the nature of service innovation and its effect on customers’ choice within the hotel industry in North Cyprus. The present study is formulated on the base of previous studies on innovation, the relationship between the innovation and tourism industry, how important it is, and the main characteristic of innovation. The study also draws attention to the different resources of innovation. Also, a sample of three-, four- and five-star hotels in North Cyprus were chosen. Then, data was gathered from 78 general managers and department managers overseeing innovation; process and outcomes. A self-administered questionnaire was used as tool for conducting quantitative research. Next, the SPSS program was utilized to measure and analyse the data. The results showed the importance of innovation which can be considered for strategic development in hotel. Though hoteliers consider innovation as an effective approach for improvement, nevertheless, they find innovations in some sectors more effective, than in some other sectors. Also the significance of innovation varies based on the three-, four- and five- star hotels. Keywords: Innovation, service innovation, customers’ choices, hotel industry, North Cyprus.

ÖZ : Çalışmanın amacı hizmet yeniliği doğasının ve bunun müşterilerin seçimi üzeridneki etkisini Kuzey Kıbrıs’taki otel endüstrisi içinde incelemektir. Çalışma; yenilik, turizm endüstrisi ve yenilik arasındaki ilişki, bu ilişkinin önemi ve yeniliğin niteliği üzerine yapılmış önceki araştırmalar temel alınarak yapılmıştır. Çalışma ayrıca yeniliğin farklı kaynaklarına da dikkat çekmektedir. Kuzey Kıbrıs’taki; üç, dört, ve beş yıldızlı oteller çalışma için seçilmiştir. Daha sonra yenilik sürecini ve sonuçlarını gözlemleyen 78 genel müdür ve bölüm amirinden veriler toplanmıştır. Niceliksel araştırma için katılımcıların kendi kendine doldurduğu bir anket kullanışmıştır. Bunu ardından very analizi için veriler SPSS’te değerlendirilmiştir. Sonuçlar; yeniliğin önemini ve otellerde stratejik bir gelişim olarak görülebileceğini göstermiştir. Otelciler yeniliği etkili bir görüş olarak algılasa da sektörden sektöre yeniliğin etkisinin değişebildiği fikrine sahiptir. Ayrıca yeniliğin anlamlı farkı üç, dört, ve beş yıldızlı oteller arasında da görülebilmektedir. Anahtar kelimeler: Yenilik, hizmet yeniliği, müşteri tercihi, otel endüstrisi, Kuzey Kıbrıs
Master of Science in Tourism Management. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Tourism, 2015. Supervisor: Prof. Dr. Hasan Kılıç.
Keywords: Tourism; Tourism - Hospitality Industry - Cyprus, North; Tourism - Management - Creative ability in business; Innovation; service innovation; customers’ choices; hotel industry; North Cyprus